Media Playout Techniques for Video Intra-Stream Synchronization: Review and Analysis (Journal of Academic Research, 2020)
Video streaming over best-effort networks is a challenging problem due to network delay and packet loss. To deal with video playout disruptions, client-side data buffering is a public and known technique. Increasing of data buffering inevitably prevents playout interruption. As a result, more memory requirement is needed and playout delay is increased. Thus, Adaptive media playout (AMP) is a client-side technique which reduces the data buffering and avoids buffer outage. The playout adaptation technique takes on the responsibility of temporal reconstruction of the stream, that is, the restoration of its intra-stream synchronization quality. This article surveys the Adaptive Media Playout techniques, aiming to succinctly merge established concepts and schemes have been proposed for the adaptation playout rate, and classify AMP techniques based on playout rate control. In addition, the pros and cons of each technique are briefly discussed. This study also deliberates challenges and issues related to video stream quality, playout rate control, adapt playout rate based on network conditions handling of buffer outage and quality evaluation metrics.
Keywords: Adaptive Media Playout; About; Multimedia Synchronization; Playout Delay; Video streaming